Stone-Free Rate and Complications Rate of Mini-Percutaneous Nephrolithotomy for Stag-Horn Stones - Khan, Ajmal; Khoso, Mujahid Ali; Muhammad Tahir; Aman Ullah; Khan Tareen, Farhaad; Khan Jogezai, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Staghorn calculi are complicated stones of the kidney, which are associated with infection and kidney deterioration. Mini-percutaneous nephrolithotomy (mini-PCNL) provides an alternative to standard PCNL that is less invasive with a possible high stone-free rates (SFR) and reduced complications. Objective: To determine the stone-free and complication rates of mini-PCNL in patients with staghorn calculi at the Armed Forces Institute of Urology (AFIU), Rawalpindi. Material and Method: It is a cross-sectional cohort study which involved 130 patients (TH-18 years) with partial or complete staghorn calculi >2 cm. Mini- PCNL was done through an 18 -20 Fr tract under fluoroscopic guidance. SFR was measured by postoperative imaging in less than 48 hours; Clavien-Dindo was used to classify the complications. Results: Mean age was 45.6 ± 11.8 years; males 58.5%. Overall SFR was 88.5% (partial: 97.6%, complete: 84.1%). Complications occurred in 15.4%, mostly mild; major complications were rare (2 cases sepsis, 1 bleeding). Conclusion: Mini-PCNL achieves high SFR with a favorable safety profile for staghorn calculi, offering an effective alternative to standard PCNL.